When a parent suffers ABI: Investigation of emotional distress in children. (3rd July 2017) - Redolfi, A.; Bartolini, G.; Gugliotta, M.; Maietti, A.; Pietrapiana, P.; Sapienza, S.; D'Amato, A.; Mazzucchi, A.
ABSTRACT: Primary objective : To investigate the type of emotional and behavioural impact that having a parent with a severe acquired brain injury (ABI) has on children during the first period of adjustment. Methods and procedure : The study involved 25 couples in which one of the spouses was affected by ABI, and their 35 children (3–14 years). The children attended three sessions with a psychologist aimed at identifying their spontaneous playing and relational behaviour by means of a grid created on the basis of ICD-10 criteria. Both members of each parental couple attended a session with the psychologist, and were administered the Dyadic Adjustment Scale, the 36-item Health Survey and the Caregiver Burden Inventory. Results : 63% of the children showed signs of emotional suffering, the presence of which was underestimated by their parents on the basis of the psychologist's assessments. The variables that correlated most closely with the children's psychological condition were related to the quality of their parents' relationship. Conclusion s: Our findings confirm the need for early interventions aimed at both parents and their children in order to investigate the children's emotional-affective situation, and favour an understanding of their discomfort by their parents.